The Evolving Landscape of Biochemical Research: From Molecules to Medicine - Al-Mobarqaa, Rajaa Mohammed (Medical Science Journal for Advance Research, 2025)
A transformation has taken place within biochemical research where out-dated practices of focusing on individual molecules and pathways without considering biological systems as a whole has changed to a practice where there is consideration for systems biology. This review looks at the history of biochemical research and trace the events that led to the innovation of the technology, their regards to changing paradigms research focus, as well as increased focus on translational research. To this end, an analysis of the transitions between classical biochemistry, modern systems biology, the effects of genomics, proteomics, metabolomics, and the shifting focus on drug and tailored medicine discovery via computation is presented.